Resilience and emotional intelligence - Rutledge, Hile (Henry Stewart Talks, 2020)
Emotional Quotient (EQ), Resilience defined, EQ as a resilience tool, Interpersonal Relationships, Social Responsibility, Self-Regard, Self-Actualization – Optimism